A quiet revolution? the rise of women managers, business owners and leaders in the Arabian Gulf States - Forster, Nick (Cambridge University Press, 2017)
An irreversible transformation is taking place in the lives of many thousands of university educated professional women in the United Arab Emirates, Oman and the Kingdom of Saudi Arabia. It also describes the vital role that women could play in the economic development and diversification of these countries, and the broader MENA region, in the future. It is an essential read for professionals, scholars and students, in fields as diverse as economic development, international management, gender studies, and Middle Eastern studies.